2020
DOI: 10.1007/s12325-020-01311-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Budesonide/Glycopyrronium/Formoterol Fumarate Metered Dose Inhaler (BGF MDI) Versus Other Inhaled Corticosteroid/Long-Acting Muscarinic Antagonist/Long-Acting β2-Agonist (ICS/LAMA/LABA) Triple Combinations in COPD: A Systematic Literature Review and Network Meta-analysis

Abstract: Introduction: Triple inhaled corticosteroid/ long-acting muscarinic antagonist/long-acting b 2agonist (ICS/LAMA/LABA) combination therapy is recommended for patients with chronic obstructive pulmonary disease (COPD) who experience further exacerbations/symptoms on dual LAMA/ LABA or ICS/LABA therapy. The relative efficacy of budesonide/glycopyrronium/formoterol fumarate metered dose inhaler 320/18/9.6 lg (BGF

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 36 publications
3
15
0
Order By: Relevance
“…The present study shows that compared with single-inhaler dual therapy, single-inhaler triple therapy significantly reduced the frequency of moderate and severe exacerbation episodes. Our results are consistent with the findings of the most recent meta-analyses [ 9 , 24 ]. In the ETHOS [ 17 ] study, which compared GLY/FOR to BUD/GLY/FOR (320 μg of budesonide), the frequency of moderate and severe exacerbation episodes decreased by 24% with BUD/GLY/FOR vs. GLY/FOR.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present study shows that compared with single-inhaler dual therapy, single-inhaler triple therapy significantly reduced the frequency of moderate and severe exacerbation episodes. Our results are consistent with the findings of the most recent meta-analyses [ 9 , 24 ]. In the ETHOS [ 17 ] study, which compared GLY/FOR to BUD/GLY/FOR (320 μg of budesonide), the frequency of moderate and severe exacerbation episodes decreased by 24% with BUD/GLY/FOR vs. GLY/FOR.…”
Section: Discussionsupporting
confidence: 93%
“…In some RCTs comparing triple therapy with dual therapy in COPD, there might be a bias resulting from the use of multiple inhaler devices. Single-inhaler therapy has been shown to improve lung function and health status [ 8 , 9 ], but evidence of a reduction in mortality with single-inhaler triple therapy versus single-inhaler dual therapy has not been well documented in previous meta-analyses.…”
Section: Introductionmentioning
confidence: 99%
“…The relevant study results were combined using a three-level hierarchical Bayesian NMA, as previously described in Ferguson et al [ 20 ]. For convenience, the methods are summarized here.…”
Section: Methodsmentioning
confidence: 99%
“…In the Phase III ETHOS (NCT02465567) and KRONOS (NCT02497001) studies, BUD/GLY/FOR showed benefits in reducing COPD exacerbations and improving lung function and symptoms versus dual LAMA/LABA and ICS/LABA therapies [ 18 , 19 ]. A recent NMA showed that BUD/GLY/FOR had similar efficacy to other ICS/LAMA/LABA fixed-dose and open combination therapies in reducing exacerbation rates, and improving lung function and symptoms at 24 weeks, in patients with moderate-to-very-severe COPD [ 20 ]. Subsequently, the recent ETHOS study has provided a large body of evidence regarding the efficacy and safety of BUD/GLY/FOR over 52 weeks [ 19 ], allowing for comparisons with other triple therapies that have been assessed in 1-year studies.…”
Section: Introductionmentioning
confidence: 99%
“…Published systematic reviews [ 12 , 13 ] and pairwise meta-analyses [ 14 17 ] on previous RCTs [ 18 25 ] claimed that triple therapy in FDCs, e.g., BDP/FF/G, FF/UMEC/VI and BUD/GLY/FF, could be better than monotherapy and dual therapy in improving lung function and quality of life. The only network meta-analysis [ 26 ] included merely seven [ 18 23 , 27 ] RCTs with 8762 participants on triple therapy in FDCs well before August 2019. It left out the 4987 participants and new findings from recent large-scale RCTs [ 24 , 25 ] on triple therapy.…”
Section: Introductionmentioning
confidence: 99%